The Library Development Based on Social Inclusion: SWOT Analysis and Socio-Religious Role - Moch Lukluil Maknun; Umi Muzayanah; Muhamad Khusnul Muna; Andjar Prasetyo; Milta Eliza (Tamaddun, 2021)
Rural libraries have an essential role in providing information services for rural communities. The heterogeneity of rural communities from social, economic, and religious aspects is the basis for the importance of social inclusion-based library services. This study uses qualitative methods to describe the implementation of an inclusion-based village Perpustakaan Muda Bhakti (Permubha) Ngablak Village, Srumbung District, Magelang Regency and its role in the social, economic, and religious life of the village community. Through a SWOT analysis, this study resulted in several research findings. First, three things become Permubha's strengths in providing services: information disclosure and access policies, communication in services, and circulation of library facilities. Second, Permubha's weakness is the unavailability of a computer-based library catalog. Third, the opportunities/opportunities that exist in Permubha are descriptive and normative officer ethics, responsibility in providing services, the role of citizen donations, and infrastructure. Fourth, Permubha has several challenges ahead in terms of service evaluation, increasing the competence and qualifications of officers, and increasing responsibilities. Fifth, in addition to library services, Permubha plays a role in social, economic, and religious activities through programs that can be participated in by the Ngablak Village community, such as the salak library program, Suluh Libraries, satellite reading, and commemoration of Islamic holidays. Perpustakaan desa memiliki peran penting dalam memberikan layanan informasi bagi masyarakat desa. Heterogenitas masyarakat desa dari aspek sosial, ekonomi, dan agama menjadi dasar pentingnya layanan perpustakaan berbasis inklusi sosial. Dengan menggunakan metode kualitatif, penelitian ini bertujuan untuk mendeskripsikan penyelenggaraan perpustakaan desa berbasis inklusi pada Perpustakaan Muda Bhakti, (Permubha) Desa Ngablak Kecamatan Srumbung Kabupaten Magelang serta perannya terhadap kehidupan sosial, ekonomi, dan keagamaan masyarakat desa. Melalui analisis SWOT, penelitian ini menghasilkan beberapa temuan penelitian. Pertama, ada tiga hal yang menjadi kekuatan Permubha dalam memberikan layanan, yaitu keterbukaan informasi dan kebijakan akses, komunikasi dalam layanan, dan sirkulasi sarana perpustakaan. Kedua, kelemahan yang dimiliki Permubha adalah belum tersedianya katalog pustaka berbasis komputer. Ketiga, peluang/kesempatan yang ada di Permubha adalah adanya etika petugas secara deskriptif dan normatif, tanggungjawab dalam memberikan layanan, adanya peran donasi warga, dan sarana prasarana. Keempat, Permubha memiliki beberapa tantangan ke depan dalam hal evaluasi layanan, peningkatan kompetensi dan kualifikasi petugas, dan peningkatan tanggung jawab. Kelima, selain layanan pustaka, Permubha berperan dalam kegiatan sosial, ekonomi, dan keagamaan melalui program-program dapat diikuti oleh masyarakat Desa Ngablak, seperti program salak pustaka, suluh pustaka, satelit baca, dan peringatan PHBI.